The effects of electron cyclotron heating and current drive on toroidal Alfvén eigenmodes in tokamak plasmas. (2nd November 2017) - Sharapov, S E; Garcia-Munoz, M; Van Zeeland, M A; Bobkov, B; Classen, I G J; Ferreira, J; Figueiredo, A; Fitzgerald, M; Galdon-Quiroga, J; Gallart, D; Geiger, B; Gonzalez-Martin, J; et al.
Abstract: Dedicated studies performed for toroidal Alfvén eigenmodes (TAEs) in ASDEX-Upgrade (AUG) discharges with monotonic q -profiles have shown that electron cyclotron resonance heating (ECRH) can make TAEs more unstable. In these AUG discharges, energetic ions driving TAEs were obtained by ion cyclotron resonance heating (ICRH). It was found that off-axis ECRH facilitated TAE instability, with TAEs appearing and disappearing on timescales of a few milliseconds when the ECRH power was switched on and off. On-axis ECRH had a much weaker effect on TAEs, and in AUG discharges performed with co- and counter-current electron cyclotron current drive (ECCD), the effects of ECCD were found to be similar to those of ECRH. Fast ion distributions produced by ICRH were computed with the PION and SELFO codes. A significant increase in T e caused by ECRH applied off-axis is found to increase the fast ion slowing-down time and fast ion pressure causing a significant increase in the TAE drive by ICRH-accelerated ions. TAE stability calculations show that the rise in T e causes also an increase in TAE radiative damping and thermal ion Landau damping, but to a lesser extent than the fast ion drive. As a result of the competition between larger drive and damping effects caused by ECRH, TAEs become more unstable. It is concluded, that although ECRH effects on AE stability in present-day experiments may be quite significant, they are determined by the changes in the plasma profiles and are not particularly ECRH specific.